2010
DOI: 10.1111/j.1447-0756.2010.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal serum high sensitive C‐reactive protein level with body mass index and severity of pre‐eclampsia at third trimester

Abstract: Elevated level of hs-CRP is a useful parameter in the severity of clinical risk of pre-eclampsia in patients with BMI < 25 kg/m(2) at third trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 33 publications
6
34
3
Order By: Relevance
“…Thirty‐two studies in total reported on C‐reactive protein levels,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 of which 17 were applicable for meta‐analysis 21, 22, 23, 29, 30, 31, 32, 33, 34, 37, 38, 39, 41, 42, 47, 49, 50. A significantly higher C‐reactive protein was found in women with pre‐eclampsia than in non‐hypertensive controls ( Figure 2), and this correlation was stronger in severe than in mild pre‐eclampsia ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐two studies in total reported on C‐reactive protein levels,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 of which 17 were applicable for meta‐analysis 21, 22, 23, 29, 30, 31, 32, 33, 34, 37, 38, 39, 41, 42, 47, 49, 50. A significantly higher C‐reactive protein was found in women with pre‐eclampsia than in non‐hypertensive controls ( Figure 2), and this correlation was stronger in severe than in mild pre‐eclampsia ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Its sensitivity is high but non specific in nature. CRP levels are elevated in healthy pregnant women compared with non-pregnant women, although to a lesser extent than that seen in PE 10 .…”
mentioning
confidence: 92%
“…10, 11 Notably, previous human studies report that circulating CRP is elevated in preeclamptic patients and its elevation is correlated to the clinical symptoms. 12, 13 Moreover, plasma CRP is found to be elevated prior to maternal disease development in patients with PE, 12, 14, 15 implicating that CRP is likely a pre-symptomatic biomarker for early detection. However, the functional role of circulating CRP in PE remains unknown.…”
Section: Introductionmentioning
confidence: 99%